2008
DOI: 10.1177/1753193408092497
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Malunion of Fractures of the Neck and Shaft of the Little Finger Metacarpal

Abstract: The outcomes of 218 little finger metacarpal shaft and neck fractures that had been treated non-operatively, with no attempt at fracture reduction, were compared with those of 44 that had been treated operatively with fracture reduction and fixation (plates or K-wires). Outcome measures included the grip strength of the little finger and the DASH score. Fracture malunion was assessed by clinical measurement of little finger ray shortening and measurement of palmar angulation on the initial radiographs. The sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…Nonoperatively treated patients were compared to those treated surgically with plates or K-wires; in the nonoperative group, there was no attempt at reduction, and the investigators found that virtually all had normal DASH scores and aesthetic scores at 2 years [49]. For patients with metacarpal neck fractures, there was no statistically significant difference between nonoperative and operatively treated patients though the data trended towards favoring the nonoperative treatment group [49]. In the case of metacarpal shaft fractures, the DASH, SportsDASH, and aesthetic scores were significantly better in the nonoperative group (p =.001, p =.009, and p =.013, respectively) [49].…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonoperatively treated patients were compared to those treated surgically with plates or K-wires; in the nonoperative group, there was no attempt at reduction, and the investigators found that virtually all had normal DASH scores and aesthetic scores at 2 years [49]. For patients with metacarpal neck fractures, there was no statistically significant difference between nonoperative and operatively treated patients though the data trended towards favoring the nonoperative treatment group [49]. In the case of metacarpal shaft fractures, the DASH, SportsDASH, and aesthetic scores were significantly better in the nonoperative group (p =.001, p =.009, and p =.013, respectively) [49].…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…A retrospective review performed by Westbrook et al examined patients with isolated small finger metacarpal neck or Initial extension lag may be seen with palmar wrist splint, which will likely resolve shaft fractures with at least 2 years of follow-up [49]. Nonoperatively treated patients were compared to those treated surgically with plates or K-wires; in the nonoperative group, there was no attempt at reduction, and the investigators found that virtually all had normal DASH scores and aesthetic scores at 2 years [49].…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…Because this shortening can theoretically lead to a decrease in power, a surgical approach has often been used in the management of these fractures to preserve metacarpal length (16). With the wide variety of open and closed surgical techniques and their effectiveness in restoring metacarpal length, surgeons tend to have a reduced threshold for selecting operative fixation of these fractures due to their fear of metacarpal shortening and its effects on power (13,16,33). Closed surgical reduction is less effective at restoring length than open techniques and, therefore, open reduction and internal fixation (ORIF) has tended to be the operative approach of choice (5).…”
Section: Discussionmentioning
confidence: 99%
“…Freehan and Sheps (8) reported that metacarpal fractures represented 42% of 72,481 reviewed cases of hand fractures. Spiral metacarpal fractures commonly result in some shortening of the metacarpal shaft (9), which may subsequently cause extension lag at the metacarpophalangeal (MCP) joint and reduced grip strength (9)(10)(11)(12)(13). Several studies have documented the relationship between shortening and hand function (1,9,12,(14)(15)(16)(17)(18)(19)(20)(21), although the maximum amount of shortening that occurs following metacarpal fracture and acceptable limits appear to be controversial.…”
mentioning
confidence: 99%
“…The additional outcome (that is, aesthetic) was expressively better for the 113 diaphyseal metacarpal fractures not treated surgically than the 26 submitted to surgery. 13 The DBUN descends along the medial side of the back of the wrist, about 4 cm beyond its proximal insertion, proximally to the wrist. It follows a deep course up to the flexor carpi ulnaris muscle, penetrates the fascia profundis and continues along the ulnar side of the back of the hand.…”
Section: Discussionmentioning
confidence: 99%